2011
DOI: 10.2478/s11658-011-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells from adipose tissue

Abstract: This is a review of the growing scientific interest in the developmental plasticity and therapeutic potential of stromal cells isolated from adipose tissue. Adipose-derived stem/stromal cells (ASCs) are multipotent somatic stem cells that are abundant in fat tissue. It has been shown that ASCs can differentiate into several lineages, including adipose cells, chondrocytes, osteoblasts, neuronal cells, endothelial cells, and cardiomyocytes. At the same time, adipose tissue can be harvested by a minimally invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 106 publications
1
73
0
4
Order By: Relevance
“…Adipose tissue stem cells can be easily harvested from adipose tissue and expanded, with capacity of differentiation on multiple lineages in vitro 21 . Many adipose tissue stem cells isolation methods have been developed since Rodbell 28 , who demonstrated that adipocytes can be isolated from the stromal vascular fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue stem cells can be easily harvested from adipose tissue and expanded, with capacity of differentiation on multiple lineages in vitro 21 . Many adipose tissue stem cells isolation methods have been developed since Rodbell 28 , who demonstrated that adipocytes can be isolated from the stromal vascular fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is easily accessible via liposuction or abdominoplasty and has been shown to contain a higher number of stem cells/progenitors than bone marrow tissue [10]. The extracted cells also expand more rapidly than those from other tissues [11]. We and other groups have shown that rat ASC can be differentiated toward a Schwann cell-like phenotype which promotes neurite outgrowth [12][13][14][15][16] and myelination [16][17][18].…”
mentioning
confidence: 99%
“…WAT specializes in energy storage and the production and decomposition of fats, thus acting as the body's metabolic reserve [5,8]. Adipose tissue is currently the focus of considerable research because it has been recognized that its stromal-vascular cell fraction (SVF) can be an abundant source of multipotent and pluripotent stem cells and adipose-derived stem cells, also called adipose tissue-derived stromal cells (ADSCs) [14,15]. WAT is a better material for the isolation of ADSCs for several reasons.…”
Section: Adipose Tissue As An Easily Accessible and Abundant Source Omentioning
confidence: 99%